STEM vs. STEAM Education and Student Creativity: A Systematic Literature Review - David Aguilera; Jairo Ortiz-Revilla (MDPI AG, 2021)
STEM (science, technology, engineering and mathematics) is an educational approach that is now accompanied by the STEAM (STEM + Arts) variant. Both educational approaches seek to renew the scientific literacy of younger generations, and, with the inclusion of the arts, student creativity is described as a key skill that must receive special attention. A review is therefore presented here of empirical STEM and STEAM-based educational interventions so as to determine their potential to develop student creativity. A systematic search of papers over one decade, 2010-2020, found 14 didactic interventions on the Web of Science and Scopus databases for analysis within the review process. The analysis suggested that: (1) the interventions based both on STEM and STEAM have multiple and even contradictory forms, both in theory and in practice; (2) there appears to be a preference among researchers for the Likert-type test to evaluate creativity; and (3) both educational approaches show evidence of positive effects on student creativity. In the light of the principal findings, it was concluded that arguing for the implementation of STEAM education over STEM education, with a view to developing or promoting student creativity, is not in agreement with the evidence from the empirical studies.